PENGEMBANGAN PRODUK ANYAMAN TAESTHIC.CO DALAM MENINGKATKAN PENJUALAN - Suyatmi Suyatmi; Diffa Maysca (Journal Competency of Business, 2021)
Indonesia has a variety of cultural diversity and handicrafts from generation to generation. Preserving the art of woven crafts which is one of the arts that must be preserved, one of which is plastic woven bags. As times change to modern times, not many people use plastic woven bags because they are considered old-fashioned and less varied. Local products are also widely abandoned because the value is not of quality and also does not vary. The lack of interest in plastic woven bags has resulted in many craftsmen losing their jobs. So Taesthic.co is here to help craftsmen in marketing their products and introducing local products. Taesthic.co was formed in February 2020 located in the Special Region of Yogyakarta which aims to collaborate with empowering craftsmen and also to develop local products of woven plastic bags in order to increase sales. The sales target of taesthic.co is women aged 25-45 years. In developing and increasing sales, Taesthic.co uses a canvas business model because it works together with plastic woven craftsmen from the Ponorogo area, emphasizing the quality and uniqueness of woven products, promotions are carried out using websites, social media and also e-commerce.